PENGARUH TINGKAT HUTANG, INTENSITAS MODAL DAN TRANSFER PRICING TERHADAP PENGHINDARAN PAJAK (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI TAHUN 2017-2021) - Sofran, Sidorus Alfandrianus; Hasanah, Neneng (Jurnal Nusa Akuntansi, 2024)
This study aims to determine the effect of the level of debt. Capital Intensity and Transfer Pricing Simultaneously on Tax Avoidance and Partial Effect of Debt Level Capital Intensity and Transfer Pricing on Tax Avoidance This type of research is quantitative in nature, and the data used are secondary data using the media in the form of financial statements of manufacturing companies taken from IDX. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2021 period, data management using eviews 9. Based on the results of the tests conducted, the debt level variable is simultaneously variable. capital intensity and transfer pricing have an effect on tax avoidance with a probability value (F-Statistic) of 0.016493 0.05. Capital intensity has an effect on tax avoidance with a probability value of 0.0018 < 0.05, transfer pricing has no effect on tax avoidance with a probability value of 0.3186 > 0.05.